Interrelationship between factors affecting job satisfaction and employee engagement among lecturers - Liang, Chooi Ling (2023)
Like any other industry, the competition in the higher education market has become extremely intense because of the proliferation of technology. Lecturers’ satisfaction and engagement with their work are the forces that drive innovation and elevate the competitive advantage for an organization’s continuous growth. Hence, this study examines the interrelationship between hygiene (pay, work-life balance and working conditions) and motivating factors (achievement, power and affiliation) affecting job satisfaction and employee engagement among lecturers in CFS, UTAR Sungai Long Campus, including assessing the mediation effect of job satisfaction between these factors and employee engagement. Data were collected from all CFS lecturers except for the three who are on maternity leave. Sixty responses out of the total sixty-three lecturers in CFS were obtained and analysed using the PLS-SEM. The findings indicated hygiene and motivating factors are the determinants of job satisfaction but not employee engagement; motivating factors are a stronger predictor of job satisfaction than hygiene factors. Job satisfaction, in turn, affects employee engagement and mediates between motivating factors and employee engagement. However, it does not have any mediation effect between hygiene factors and employee engagement. Conclusively, motivating factors are the more important determinants of lecturers’ job satisfaction and thus enhance employee engagement. A fairer appraisal system and a clear career path should be designed to motivate lecturers who perform and have the potential to continue contributing to the centre. Strategic teams and exchange programs can be formed to provide recognition and a platform for lecturers to showcase their talents. Having a dialogue group encourages two-way communication and increases commitment from the joint decision made. Besides, teamwork can be cultivated for organising activities to build rapport among lecturers. Job satisfaction embeds positive feelings inside the lecturers and thus connects them to work with full dedication and enthusiasm. Most studies analysed the direct effects on job satisfaction rather than its role as a mediator. This study presents the direct and indirect effects, thus untying some knots from a more complex and intriguing perspective.